2021
DOI: 10.1002/ldr.4131
|View full text |Cite
|
Sign up to set email alerts
|

No significant change noted in annual nitrous oxide flux under precipitation changes in a temperate desert steppe

Abstract: As the third most important greenhouse gas, nitrous oxide (N 2 O) poses a significant threat to global warming and the ozone layer. However, the effects of precipitation changes on N 2 O emissions in arid areas remain unclear, particularly in desert steppe environments. Therefore, an in situ control experiment was conducted from July 2018 to July 2020 to examine the N 2 O emissions with changes in precipitation in the Urat Desert Steppe, northwestern China. The results showed that the N 2 O emission rate was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The N 2 O produced during N transformation process is an important source of greenhouse gas, and therefore, the response of N 2 O emissions to precipitation changes is a topic of interest (Yue et al, 2022). The abundance of nosZ , a key gene involved in denitrification, represents the capacity for the transformation of N 2 O to N 2 (Petersen et al, 2012), and a higher ratio of ( norB + norC )/ nosZ abundance implies a higher potential for N 2 O release (Wang, Su, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The N 2 O produced during N transformation process is an important source of greenhouse gas, and therefore, the response of N 2 O emissions to precipitation changes is a topic of interest (Yue et al, 2022). The abundance of nosZ , a key gene involved in denitrification, represents the capacity for the transformation of N 2 O to N 2 (Petersen et al, 2012), and a higher ratio of ( norB + norC )/ nosZ abundance implies a higher potential for N 2 O release (Wang, Su, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of increased N deposition on soil N 2 O emissions was suggested to result from the accelerated N cycling process. Previous studies reported positive and neutral effect of additional water supply on soil N 2 O emissions [11][12][13][14][15]. This varied response of N 2 O emissions to additional water was suggested to depend on the types of grassland and the quantity of treatments [16].…”
Section: Introductionmentioning
confidence: 94%
“…Soil N transformations are driven by functional microorganisms (Daims et al, 2015) such as ammonia-oxidizing microorganisms, which specifically affect the soil nitrification process (Yue et al, 2021(Yue et al, , 2022. Complete ammonia oxidizers (comammox) can oxidize NH 4 + -N directly to NO 3 À -N, rather than via two steps (oxidation of ammonia to nitrite and nitrite to nitrate) which is the traditional view of nitrification (Daims et al, 2015).…”
Section: Introductionmentioning
confidence: 99%